Effect of Modulated Alternating and Direct Current Iontophoresis on Transdermal Delivery of Lidocaine Hydrochloride. (15th May 2014) - Bhatia, Gaurav; Banga, Ajay K.
Abstract : The objective of this study was to investigate the iontophoretic delivery of lidocaine hydrochloride through porcine skin and to compare the effects of modulated alternating and direct current iontophoresis. Continuous and modulated iontophoresis was applied for one hour and two hours (0-1 h and 4-5th h) using a 1% w/v solution of lidocaine hydrochloride. Tape stripping was done to quantify the amount of drug permeated into stratum corneum and skin extraction studies were performed to determine the amount of drug in stripped skin. Receptor was sampled and analyzed over predefined time periods. The amount of lidocaine delivered across porcine skin after modulated direct current iontophoresis for 2 h was 1069.87 ± 120.03 μ g/sq·cm compared to 744.81 ± 125.41 μ g/sq·cm after modulated alternating current iontophoresis for 2 h. Modulated direct current iontophoresis also enhanced lidocaine delivery by twelvefold compared to passive delivery as 91.27 ± 18.71 μ g/sq·cm of lidocaine was delivered after passive delivery. Modulated iontophoresis enhanced the delivery of lidocaine hydrochloride across porcine skin compared to the passive delivery. Modulated alternating current iontophoresis for duration of 2 h at frequency of 1 kHz was found to be comparable to the continuous direct current iontophoresis for 1 h.